2018
DOI: 10.1111/cogs.12668
|View full text |Cite
|
Sign up to set email alerts
|

How Do Creative Experts Practice New Skills? Exploratory Practice in Breakdancers

Abstract: How do expert performers practice as they develop creatively? This study investigated the processes involved in the practice of new skills by expert breakdancers. A great deal of evidence supports the theory of "deliberate practice" (Ericsson, Krampe, & Tesch-Römer, 1993, Psychological Review, 100, 363) in skill acquisition; however, expert creative performers may emphasize other forms of practice for skill development. Four case studies collected through fieldwork and laboratory observation were analyzed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
(107 reference statements)
1
13
0
Order By: Relevance
“…Regarding these questions, using in‐depth analysis of dancers’ practice, Shimizu and Okada (2018) revealed that expert breakdancers engaged in “exploratory practice” to generate new and original skills. They claimed that “The dancers practiced with multiple goals, that is, not only to improve the quality of the skills but also to develop original and flexible skills that fit well into a performance by varying aspects of domain skills and by combining those domain skills with other domain skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding these questions, using in‐depth analysis of dancers’ practice, Shimizu and Okada (2018) revealed that expert breakdancers engaged in “exploratory practice” to generate new and original skills. They claimed that “The dancers practiced with multiple goals, that is, not only to improve the quality of the skills but also to develop original and flexible skills that fit well into a performance by varying aspects of domain skills and by combining those domain skills with other domain skills.…”
Section: Discussionmentioning
confidence: 99%
“…They claimed that “The dancers practiced with multiple goals, that is, not only to improve the quality of the skills but also to develop original and flexible skills that fit well into a performance by varying aspects of domain skills and by combining those domain skills with other domain skills. Thus, the expert breakdancers practiced by employing a highly exploratory and creative process” (Shimizu & Okada, 2018, p. 2392). The importance of the integration of knowledge and skills in other domains, encounters with the outside, inspiration, and serendipity in creativity, has been discussed (see Austin, 2003; Duggan, 2007; Ishiguro & Okada, 2018, 2020; Okada & Ishibashi, 2017; Roberts, 1989; Stokes & Gibbert, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamical methods (e.g., recurrence analysis) are also expected to reveal the creative process in detail using more advanced techniques (e.g., the windowed sliding method; Coco and Dale, 2014;Kodama et al, 2018). We also aim to apply the framework not only to experimental situations but also to more ecological situations, such as the practical field of artistic performance, natural daily interaction (D'Ausilio et al, 2015;Dale, 2015;Sekine and Kita, 2015;Shimizu and Okada, 2018) and clinical interaction in psychological and medical fields (Zivotofsky and Hausdorff, 2007;Nagaoka and Komori, 2008;Ramseyer and Tschacher, 2011;Goldstein et al, 2020) involving speech-motion coordination in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of novices' art creation showed that by incorporating others' perspectives by copying others' artwork, people can change their own perspective of creation and generate novel works (Okada & Ishibashi, 2017). As for the third component, studies on the development of creative expertise suggest that the long-term exploratory process plays a critical role in the creative expertise development (Okada, Yokochi, Ishibashi, & Ueda, 2009;Shimizu & Okada, 2018;Yokochi & Okada, 2020). We have previously mentioned the details of this component.…”
Section: Figure 1 Outline Of the Creativity Dynamics Approach Framework By Repeating This Dynamical Developmental Process People Graduallmentioning
confidence: 99%
“…Among the various aspects of creativity, we focus on supporting the process of developing creative concepts and visions connected firmly to the participants' own lives and values. Studies investigating the development of the creative expertise of dancers suggest that they exploratorily generate various types of expressions that expand existing repertoires of expression in the domain (Shimizu & Okada, 2018). Moreover, they develop their own interpretations of expression through this exploratory process (Shimizu & Okada, 2020).…”
Section: Introductionmentioning
confidence: 99%